PERAN PENANGGUNG JAWAB REKAM MEDIS (PJRM) UNTUK PENINGKATAN KETEPATAN KLAIM BPJS PASIEN RAWAT INAP DI RSUD KRMT WONGSONEGORO (RSWN) KOTA SEMARANG - Retno Astuti Setijaningsih; Suyoko - -; Nova Dhea Ammar N; Supriyatiningsih - - (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Medical Record Document (MRD) guarantees patient safety. Besides, it related to claim accuracy to BPJS (Badan Penyelenggara Jaminan Sosial) as patient health insurance operator. In fact, from the survey conducted with 15 inpatients as the subjects, 10 MRD approved (approximately 66.67%) and the other 5 MRD or about 33.34% rejected. This happened as the consequences of whether supporting examination result which is not being submitted on 2 MRD (40%), 1 MRD or 20% hold incomplete BPJS document and other 40% caused by the inaccurate operation code in MRD. Hence, the aim of this study is to analyze the role of Person In Charge in Medical Record Department to improve MRD comprehensiveness to reach BPJS claim accuracy.The type of this study is qualitative with cross-sectional approach. Primary and secondary source observation and interview are used in collecting data. Purposive sampling with four interviewees from Person In Charge in Medical Record Department, and as the main interviewee is the head of Medical Record Department also one employee of BPJS Rumah Sakit Wongsonegoro as the triangulator.So, the main function of assembling employee is to ensure the quality of Medical Record Document (MRD), quantitatively and qualitatively. Whereas, RSWN already applied Person In Charge of Medical Record Department with concurrent analysis in controlling MRD comprehensiveness concept. According to observational result of 15 inpatients, found incomplete MRD, 13% occurs in identity section, also 13% each found both in recording and reporting. While, the authentication completes 100%. From consistency analyzing result discovered inconsistency recording about 13%. Main diagnose and inform consent recording reached 100% in consistency and 0% things that can cause loss.That is, the role of Person In Charge in Medical Record of inpatient unit needs yo be improved. The main and assembling function performs by PIC in Medical Record is both coding and indexing. Input standard, Standard Operational Procedures (SOP) and minimum services standard are already available and applied to control PIC in Medical Record performance quality. However, input, process and the output are not focus in controlling MRD comprehensiveness yet, especially in BPJS participant patient. So that, to control BPJS inpatient MRD quality, needs operational standard in methods and comprehensiveness control procedures, considered with PIC in Medical Record also performing ICD code and Medical Record Document quality requires coordination of all parties.The researchers suggest to add more points in controlling incomprehensiveness BPJS Medical Record Document procedures. Furthermore, enhance input in standard structure, operational job description in Standard Operational Procedure, also minimum services standard comprehensiveness which applied has to be reached 100% qualitatively and quantitatively.Keywords: PIC in Medical Record, BPJS claim, quantitative comprehensiveness, qualitative comprehensiveness